Gerald Murnane’s Transnational Reception - Stinson, Emmett (Mémoires du livre / Studies in Book Culture, 2025)
Gerald Murnane retired from writing in 1995. His experimental fiction had never won major awards or sold well. In 2009, he published a new novel, Barley Patch. Murnane subsequently become an international success who was profiled in The New York Times and The New Yorker (twice). He could claim major writers—J. M. Coetzee, Jon Fosse, Joshua Cohen, Teju Cole, and Ben Lerner—as admirers, and had high prestige publishers in the US, the UK, and Australia. How did Murnane go from cult author to a major international writer? This essay tracks the material reception of Murnane’s post‑retirement writing, and the network of actors who boosted his reputation. It presents an account of the way that highbrow literature is transmitted transnationally and compares this to Lawrence Rainey’s account in Institutions of Modernism (1998) to understand how online reception has changed the way that highbrow literary authors are made visible to readers.